Teacher Reflective in Online Learning during Pandemic: The Case of Indonesia - Naili Zaqiya (Graduate Program, University of Islam Malang, 2021)
AbstractReflective practice is the essential part of learning process, especially in the online learning during pandemic. This is become the way of teachers to assess the effectiveness of learning and figure out what the challenges hindering the learning process are in order to optimize the learning process. This study employs a qualitative approach, in which researchers attempt to explain a phenomenon by focusing on the big picture rather than breaking it down into factors. Data was gathered mostly through questionnaire. The data was derived from three teachers that meet the requirement of this research through unstructured interviews via google form. The findings of this study show that teacher reflection is used to renew teaching method methods in the teaching and learning process, resulting in a more effective and conducive classroom environment. Furthermore, the practice of reflection aids instructors in becoming more creative and imaginative in order to improve teacher effectiveness when implementing online learning in the classroom. Keywords: Reflective Practice, Online Learning, Teacher Performance